(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Security challenges such as militancy, kidnapping, oil theft, and communal conflicts threaten stability in South-South Nigeria. Traditional kinetic security measures, while providing temporary relief, fail to address the root causes of insecurity, perpetuating cycles of violence. This study critically examines the role of intelligence gathering and non-kinetic strategies in crime control, emphasizing their potential to transform the region’s security landscape. Non-kinetic approaches, including socio-economic empowerment, community engagement, and conflict resolution, target underlying drivers like poverty, unemployment, and environmental degradation. Using a mixed-methods design, findings highlight the effectiveness of grassroots intelligence gathering, skill empowerment initiatives, and advocacy programs, such as school-based crime prevention clubs, in reducing criminal behavior. Guided by Routine Activities and Social Disorganization Theories, the study recommends prioritizing vocational training, enhancing community-police collaboration, and implementing conflict resolution mechanisms. These strategies offer a sustainable pathway to peace and security in South-South Nigeria.